Structural studies of self-assembled Cu(II), Ni(II) and Cd(II) coordination polymers fabricated with amine ligands and dicarboxylic acid linkers / Wannur Sofiasalamah Khairiah Ab Rahman - Wannur Sofiasalamah, Khairiah Ab Rahman (2017)
Self-assembly process of Cu(II), Ni(II) and Cd(II) metal ions using ethylenediamine (en) or o-phenylenediamine (o-phen) ligands with adipic (L1) or teraphtalic acid (L2) linkers respectively in solution resulted unexpected coordination polymers and one dimeric complex. A total of seven crystals were successfully obtained; [Cu(en)(L1)]∙L1H2 (1), [Cu(en)(L2)(H2O)2] (2), [Ni(en)(L1)(H2O)2]∙H2O (3), [Ni(o-phen)2(L2)] (4), Ni2(en)2(L2)2(H2O)] (5), [Cd(en)(L2)(H2O)] (6), and [Cd2(o-phen)2(L1)(Cl)2(H2O)2] (7) showing different molecular structures and crystal packing. Structural studies revealed the incorporation of the different carboxylate moiety as linkers which led to 1-dimensional zig-zag chains for 1 and 2, 1-dimensional linear chains for 3 and 4, 3-dimensional chains for 5, 2-dimensional chains for 6 with a dimeric molecular structure for 7. The series outlined the principle of crystal engineering and supramolecular chemistry where crystal structures are always unpredictable. All structures were dominated by the persistent hydrogen bonding as the primary synthon. The coordination entity also were confirmed by using IR spectroscopy. PXRD patterns showed consistency between the bulk materials with the calculated pattern generated using SCXRD data.